Efektivitas Layanan E-Counseling dalam Membantu Permasalahan Siswa Selama Masa Pandemi Covid-19 - Handika, Mardy; Herdi, Herdi (Jurnal Paedagogy, 2021)
The purpose of this study was to describe the effectiveness of e-counseling services in helping students’ problems during the Covid 19 pandemic. The method in this study was a literature study, namely by collecting reading material from various scientific articles and then comparing theories and research results, which were then analyzed descriptively. . Based on the results of a literature study conducted that the implementation of online counseling (e-counseling) is effective in helping the problems faced by students, where during the Covid 19 pandemic there are many obstacles or problems faced by students so that this matter needs to be responded to by BK teachers / Counselor through the provision of online-based counseling services (e-counseling).